(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
To assess the quality of sweetened condensed milk of Bangladesh four different brands of sweetened condensed milk were selected viz. Danish, Fresh milk, Star ship and Goalini. Twenty samples were analyzed for physical (organoleptic), chemical and microbiological qualities. From the physical test it was observed that all samples were in good grade i.e. fresh, free from odour, viscous and smooth, rich cream to yellow in colour and very sweet in taste. The average physical score was 88.05±7.631. Sweetened condensed milk had a titrable acidity of 0.135 to 0.180 %; fat 6.80 to 8.0 %; protein 6.51 to 7.96 %; ash 1.50 to 1.83 %; carbohydrate 53.74 to 55.62 % and total solids (TS) 69.98 to 73.15 %. The total viable count was in the range of 10x102 to 20x102 CUF/g; no coliform bacteria were found. The results of acidity percentage, fat content, organoleptic tests and microbiological tests indicated that there was no variation among different brands of sweetened condensed milk. But, when other chemical parameters (protein, ash, carbohydrate and total solids) were considered then Star ship was found to be better than that of Danish, Goalini and Fresh milk. Bangladesh J. Sci. Ind. Res. 42(2), 147-156, 2007